Yabancı sermayenin Türkiye’ye geliş yolları - Yazan, Ferit (My University, 2006)
TEZ ÖZETİ Yabancı Sermayenin Türkiye’ye Geliş Yolları Günümüzün küreselleşen dünyasında izolasyon sağlanarak kendi kabuğuna çekilmenin imkansız olmasından dolayı, önemli olan entegrasyonun vazgeçilmezliğinin kabul edilerek bu sistemde gerekli kuralların ülke lehine olacak şekilde belirlenerek sistemden yararlanmaktır. Yabancı sermaye ile ülkenin karşılıklı çıkar ilişkisi göz önünde bulundurulmalıdır. Yabancı sermaye, son dönemlerde ülkemizin ekonomisi açısından giderek önem kazanan bir hal almıştır. Bununla birlikte küreselleşen dünyadaki gelişmelere paralel olarak yabancı sermaye konusundaki hukuksal düzenlemelerde de değişiklik yapılması ihtiyacı ortaya çıkmıştır, varolan yasalarda yenilemelerde bulunulmuştur. Ülkemizde faaliyette bulunan yabancı sermayeli şirketlerin ülkemizdeki yatırımlarını arttırmaları amaçlanmakla beraber daha önce ülkemize gelmemiş olan yabancı sermayenin ülkemize çekilmesi için imkanlar yaratılmaya çalışılmaktadır. Genel olarak ekonomik bağlamda ele alınan bu hususun hukuksal bakımdan da önem taşıdığı bilinmektedir. Bu noktadan hareket edilerek yabancı sermayenin Türkiye’ye yatırım yaparken izlediği yollar hukuksal olarak ele alınmıştır. Yapılan çalışmada daha önce yabancı sermaye konusunda ele alınmayan veyahut yeterli miktarda bahsedilmeyen hususlar ele alınarak incelenmiş incelemeler ışığında bir sonuca varılmaya çalışılmıştır.

The Arrival Ways of Foreign Capital to Turkey In todays global world, it’s impossible to be izolated from the other countries. It’s important that to accept the indispensablity of integration and to benefit from the system. It’s known that there is a mutually benefit relationship between the foreign capital and the country. In last period the foreign capital became important for the economy of our country. By this, in the parallel of developments in globalized world its needed to make some changings in law. It’s wanted to increase the capital of the multinational companies in our country and it’s wanted to inflect the foreign capital that didn’t come to our country before. It’s known that in economic bundle this subject is very important in legal perspective. From this point the arrival ways of the foreign capital to Türkiye was discussed by legal. In this thesis the subjects about foreign capital was observed and according to the observations we wanted to reach to a reason. (MAKE ATTRACTİVE)çekmek çekmek: abide, abstract, appeal, attract, bear, beguile, brook, captivate, drag, draw, endure, enthrall, experience, extract, haul, inflect, know, lure, magnetize, pull, shrink, undergo, unfurl, weigh, withdraw, to pull, to draw, to drag, to haul, to tug, to lug, to tow, to withdraw, to hoist, to extract, to carry, to support, (silah vb.) to draw, to pull out, to suffer, to undergo, to bear, to endure, to abide, to put up with, to absorb, to inhale, to shrink, to içmek, (resim) to take, (kahve, vb.) to grind öğütmek, (film) to shoot, (bayrak) to run up, (ilgi, dikkat) to catch, to conjugate, to decline, to weigh, to attract, to magnetize, to charm, to captivate, to appeal, to beguile, to distil, (kablo, vb.) to lay döşemek, (dayak, vb.) to give, to give a meaning, to interpret, to last, to take, to drive, to put on, to wear, to pull on, to draw on giymek, (boya) to apply çekmek 1. / ı/ to pull. 2. / ı/ to draw; to haul, drag, tug. 3. / ı/ (for an animal) to pull, draw (a vehicle). 4. / ı/ to pull on (one's boots, trousers). 5. / ı/ to tow. 6. / ı/ to draw (a weapon). 7. / ı/ to pull, extract (a tooth). 8. / ı/ to attract, draw. 9. / ı/ to absorb. 10. / ı/ (for someone) to inhale, breathe in, inspire (air, smoke); (for a machine, an opening) to suck in, pull in, draw in (air, smoke, a liquid). 11. / ı/ to support, bear, take, carry (a weight, a load): Bu sütun o ağırlığı çekmez. This pillar won't carry that weight. 12. / ı/ to bear (an expense). 13. / ı/ to bear, endure, put up with, suffer (an illness, pain, sorrow, trouble, a troublesome person). 14. / ı, dan, a/ to take (a harvest) from (the fields) to (a granary, a storehouse). 15. / ı, dan/ to withdraw (a product) from (a market). 16. / ı, dan/ to withdraw (money) from (a bank). 17. / ı, dan/ to get (someone) to give up (a bad habit). 18. / ı, dan/ to clear (goods) through (customs). 19. / ı, dan/ to draw (water) from (a well). 20. / ı/ to distill. 21. (for a chimney) to draw. 22. / ı/ to draw (a line). 23. / ı, a/ to apply (kohl) to. 24. / ı/ to build (a fence, a wall, a barrier); to string up (a curtain). 25. / ı/ to hoist (a flag). 26. / ı/ to lay (a cable); to stretch, string up (a wire, a rope). 27. to weigh, have a weight of; / ı/ to weigh, measure the weight of. 28. / ı/ to draw (lots, chances) (in a lottery). 29. / a, ı/ to send (someone) (an official notice, a telegram, a fax). 30. / ı, a/ to interrupt (someone's words) in (a specified way). 31. / ı/ to take (a photograph); cin. to shoot (a movie). 32. / ı, da/ to sew (something) on (a sewing machine). 33. / ı/ to grind (coffee, etc.). 34. / ı, a/ to put (one animal) together with (another) so that they will mate. 35. / a/ (for one person) to resemble, take after (another). 36. (for cloth) to shrink. 37. / a, ı/ to give (something) (a coat of paint). 38. / a, ı/ to give (someone) (a beating). 39. / ı/ gram. to conjugate (a verb); to decline (a noun). 40. (for a month) to be (a specified number of days) long; / dan/ (for one place) to be (a specified amount of time) away from (another). 41. / ı/ to deliver, make (a speech). 42. / ı/ to give (a banquet). 43. / ı/ to repair a run in (a woman's silk or nylon stocking). 44. slang to drink, down (an alcoholic beverage). 45. / a/ slang (for one player or team) to score (points, goals) against (another player or team). 46. / ı/ slang to fill (a specified number of glasses) with (tea, beer, etc.) (used by waiters and barmen): İki çay çek! Give me two teas! 47. / a/ slang to hit, sock (someone): Yüzüne öyle bir çekerim ki! I'll give you a wallop you won't forget! Çek!/ Çek arabanı! colloq. Clear out!/ Get out! çekip çekiştirmek / ı/ to backbite (someone). çekip çevirmek / ı/ 1. to run, manage (a place). 2. to get things running smoothly in (a place). 3. to manage (people). 4. to straighten (someone) out; to set (someone's house) in order. çekip gitmek to leave, clear out; to slip away. Çekiver kuyruğunu! slang Forget about him/ her/ them (as he/ she/ they will be of no use to you)! çekeceği olmak / dan/ (for someone, something) to be a real pain for, make life unpleasant for (used only to refer to the future): Ondan çekeceğimiz var! He's going to be a real pain! Die Einfuhrwege des Ausländischen Kapitals in die Türkei Da in der heutzutage globalen Welt, es unmöglich ist, sich durch isolation in ein geschlossenes Feld zu ziehen und es von hoher Wichtigkeit ist, die unverzichtbare Integration zu akzeptieren. und vom System möglichst hohen Profit durch die Normen, welche zugunsten des Landes sind gebrauch zu machen. Der gegenseitige Profit des Landes und des fremden Kapitals muß stets beachtet werden. Das Fremdkapital hat in unserer Wirtschaft in der letzten Zeit mehr und mehr an Bedeutung gewonnen. Und damit parallel betrachtet, ist es erforderlich, dass der Bedarf gesetzlicher Regelungen neu behandelt werden muß, und dadurch die bestehenden Gesetze erneuert wurden. Damit die in unserem Land tätigen Firmen mit fremden Kapital ihre Investitionen erweitern und andere Firmen welche noch nicht in unserem Land tätig sind, mit Investitionen beginnen werden Möglichkeiten erschaffen. Im generellen als wirtschaftlich behandeltes Thema, ist es aber auch bekannt, dass die Gesetzliche Perspektive von hohem Wert ist. Von diesem Blickpunkt aus betrachtet, wurden die Wege welche das Fremdkapital beim investieren benutzt, von einer juristischen Perspektive behandelt. Das Ziel dieser Arbeit war, zuvor noch nicht behandelte oder zuwenig behandelte Themen im Rahmen des Fremdkapitals zu erfassen und an Schlußfolgerungen zu gelangen.
Keywords: Yabancı Sermaye_Türkiye